Detection of Viable but Nonculturable Escherichia coli O157:H7 in Ground Beef by Propidium Monoazide real-time PCR - Jehan Mahmoud Mahmoud Ouf; Yuan Yuan; Prashant Singh; Azlin Mustapha (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
Escherichia coli O157:H7 can enter into a viable but nonculturable (VBNC) state under stress conditions. Pathogens in this dormant state may escape detection if conventional methods are employed, and potentially pose serious threats to human health. Studies have shown that many intervention and preservation processes that are commonly used in the food industry may instead induce a VBNC state rather than kill the intended pathogens. This study aimed to detect whether E. coli O157:H7, an important and dangerous foodborne pathogen, could adapt to the stress caused by lactic acid exposure by entering the VBNC state. A propidium monoazide (PMA) quantitative PCR (qPCR) method was used for detection and quantifi cation of VBNC E. coli O157:H7 cells. The performance of this PMA-qPCR method was assessed using pure culture and ground beef samples inoculated with VBNC E. coli O157:H7 cells. The applied assay could detect as low as 103 CFU/mL VBNC E. coli O157:H7 in pure culture and 4 × 104 CFU/g VBNC cells in ground beef. Results indicate that PMA qPCR could accurately quantify E. coli O157:H7 in a VBNC state.